The Effect of Progressive Muscle Relaxation (PMR) on Stress Level of Diabetes Mellitus Patients - Lutfi Wahyuni; Catur Prasastia Lukita Dewi (Journal of Ners and Midwifery, 2024)
Diabetes mellitus is a chronic condition that occurs when there is an increase in glucose levels in the blood because the body cannot produce enough insulin or use insulin effectively. In stressful conditions, it can increase the hormone adrenaline which can convert glycogen reserves in the liver into glucose and increase blood sugar in diabetes mellitus patients. The objective of this research was to prove the effect of Progressive Muscle Relaxation (PMR) on stress levels in Diabetes Mellitus patients. Research design pre-post test control group design. The experimental group was given treatment in the form of progressive muscle relaxation (PMR) while the control group received treatment as usual/conventional. The samples in this research were some DM patients at the Mentikan Community Health Center, Mojokerto City, totaling 35 respondents. The results of the pre-test and post-test in the treatment and control groups showed that there was a reduction in stress. It was found that there was a significant decrease in stress in both the treatment group, this was indicated by p=0.001 for the treatment group, while in the control group it was found to be p=0.303, so the decrease stress is not significant. After carrying out PMR, it is hoped that the client will be able to manage the body's condition in response to stress.